Adaptive phenotypic response to climate enabled by epigenetics in a K-strategy species, the fish Leucoraja ocellata (Rajidae). Issue 10 (October 2016) - Lighten, Jackie; Incarnato, Danny; Ward, Ben J.; van Oosterhout, Cock; Bradbury, Ian; Hanson, Mark; Bentzen, Paul
Abstract : The relative importance of genetic versus epigenetic changes in adaptive evolution is a hotly debated topic, with studies showing that some species appear to be able to adapt rapidly without significant genetic change. Epigenetic mechanisms may be particularly important for the evolutionary potential of species with long maturation times and low reproductive potential ('K-strategists'), particularly when faced with rapidly changing environmental conditions. Here we study the transcriptome of two populations of the winter skate ( Leucoraja ocellata ), a typical 'K-strategist', in Atlantic Canada; an endemic population in the southern Gulf of St Lawrence and a large population on the Scotian Shelf. The endemic population has been able to adapt to a 10°C higher water temperature over short evolutionary time (7000 years), dramatically reducing its body size (by 45%) significantly below the minimum maturation size of Scotian Shelf and other populations of winter skate, as well as exhibiting other adaptations in life history and physiology. We demonstrate that the adaptive response to selection has an epigenetic basis, cataloguing 3653 changes in gene expression that may have enabled this species to rapidly respond to the novel environment. We argue that the epigenetic augmentation of species evolutionary potential (its regulation though gene expression) can enable K-strategists to survive and adapt to different environments, and this mechanism may be particularly important for the persistence of sharks, skates and rays in the light of future climate change.